LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK MODELING UNTUK MENINGKATKAN SELF ESTEEM SISWA KELAS VIII MTSN 6 CIANJUR - Kaesar Irham Nafillah, kaesarbk2020; Sobari, Teti; Ayu Ningrum, Devy Sekar (IKIP Siliwangi, 2025)
This study aims to determine the effectiveness and implementation of group guidance services with modeling techniques in improving students' Self esteem and the obstacles faced by teachers and students in class VIII MTsN 6 Cianjur. The level of success of group guidance services with modeling techniques in increasing students' Self esteem, which refers to the phenomenon of students who have low Self esteem such as not believing in themselves, and lack of acceptance from others. This research method is Mix Mtehods using The Explanatory Sequential Design with One Group Pretest- Posttest Design. The subjects in this study were class VIII students of MTsN 6 Cianjur consisting of 10 students. The sampling technique used in this study used purposive sampling technique. The measuring instrument in this study used a Likert scale, and the results of the Cronbach's alpha reliability test were 0.899. Based on the results of the paired t-test test, it is 0.001 <0.05, this shows that the Ho hypothesis is rejected and Ha is accepted, which means that group guidance with modeling techniques is effective in increasing the Self esteem of class VIII students at MTsN 6 Cianjur so it can be concluded that the application of group guidance services with modeling techniques is effective in increasing the Self esteem of class VIII students at MTsN 6 Cianjur.